Synthesis, crystal structure, and Hirshfeld surface analysis of undecacarbonyl{tris[4-(methylsulfanyl)phenyl]arsine}-triangulo-triosmium(0) - Siti Syaida Sirat; Mohd Mustaqim Rosli; Sang Loon Tan; Ibrahim Abdul Razak; Omar bin Shawkataly (Acta Crystallographica Section E: Crystallographic Communications)
The title compound, [Os3(C21H21AsS3)(CO)11] or [Os3{As(C6H4SCH3)3}(CO)11], comprises a triangle of Os atoms, two of which are bonded to four carbonyl ligands. The third Os atom is bound to three carbonyl ligands, and the arsine ligand [As(C6H4SCH3)3] occupies the equatorial position. In the crystal, the molecules are linked by C—H...O hydrogen bonds. To further analyse the intermolecular interactions, a Hirshfeld surface analysis was performed. Two out of the three methylsulfanyl groups are disordered over two sites with final refinement occupancy ratios of 0.612 (12):0.388 (12) and 0.620 (9):0.380 (9).